Tubercles of transverse process of atlas with its developmental correlations - Gopal, Krishna; Anurag, .; Agarwal, Jolly (International Journal of Research in Medical Sciences, 2017)
Background: Atlas is the first cervical vertebra. The transverse process of atlas homologous with the posterior tubercle of the transverse process of a typical cervical vertebra. There is a controversy about the development of the tip of the transverse process of atlas vertebra. Methods: The 300 human dry atlas vertebra or 600 transverse processes were selected from the anthropology museum of department of anatomy, SRMS medical college Bareilly and SGRRIM &HS Dehradun, Uttaranchal, India. The age and sex of the vertebrae were not taken into consideration. The tip of the Transverse process of atlas vertebrae was examined for its variants like having anterior and posterior tubercles like the typical cervical vertebrae. Results: The anterior and posterior tubercles of the transverse process and the status of foramen transversarium were observed in 300 atlas vertebrae. In 1.33% of specimen the tips of the transverse process having bilateral anterior and posterior tubercles. In 0.83% of specimen transverse process having anterior and posterior tubercles on the left side and in 1% on the right side. The total percentages of transverse processes with anterior and posterior tubercles were found in 3.17% of specimens. Conclusions: In present observation the tip of the transverse process of atlas presenting the feature of a typical cervical vertebra (with Anterior and posterior tubercles) observed in 3.17% of specimen. This study may be helpful for the embryologist, neurosurgeons and orthopedic surgeons.